(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Sthaulya (obesity) is so profound disease spreading worldwide and is associated with various systematic diseases. Sthaulya is mainly a lifestyle disorder occurring due to our eating habits of preserved and processed food items or it may have some genetic aetiology. Aim: To assess the efficacy of drug Musta along with Pathya-Apathya for 90 days. Material and Method: The subject has been selected from OPD with symptoms of Sthaulya and regular assessment has been done every 15 days at Ayurvedic and Unani Tibbia College and Hospital Karol Bagh. Drug Musta Churna (Cyperus rotundus) is administered orally with Pathya-Apathya for 90 days. At the end of the study, all data information related to the subject before and after treatment like weight, height, BMI measurement, and skin fold thickness of various regions and Lipid profile has been documented. Discussion: Before and after the treatment of the study subjective and objective parameters are thoroughly analysed and it has been found that there are practical changes in various parameters with no side effects. Conclusion: It has been concluded that single Musta churna is highly effective in Sthaulya along with Pathya-Apathya.